Gestational and perinatal outcomes in recurrent miscarriages couples treated with lymphocyte immunotherapy - Manoel Sarno; Marcelo Borges Cavalcante; Marla Niag; Kleber Pimentel; Ivana Luz; Bianca Figueiredo; Tatiana Michelon; Jorge Neumann; Simone Lima; Isabela Nelly Machado; Edward Araujo Júnior; Ricardo Barini (Elsevier, 2019)
Objective: This study aims to elucidate which types of recurrent miscarriage (RM) patients experienced a livebirth after paternal lymphocyte immunotherapy (LIT) and to evaluate the perinatal outcome. Study design: Retrospective analysis of a multicenter, observational study which enrolled 1096 couples with a history of two or more spontaneous miscarriages without any intercalated delivery. We conducted an intention-to-treat analysis of couples with RM treated with or without LIT regarding to gestational and perinatal outcomes. We compared groups by using the Student's t-test or Kruskal-Wallis test, Fisher's exact-test and χ2 test when appropriate. Results: The success of gestation was significantly higher in the LIT group (60.1% vs. 33.1%; p <  0.001). A sub-analysis of four different immune disorder groups revealed a significantly higher success in the LIT group in all immune categories, except in patients who had autoantibodies positive. We observed no significant differences in perinatal outcomes such as gestational age at birth, preterm and extreme preterm birth, and birth weight in successful pregnancy in both groups. The success rate was significantly higher when LIT was administrated before and during pregnancy and only during pregnancy compared to only before pregnancy (p <  0.01). Conclusions: Careful laboratory test phenotyping of RM patients may identify subgroups most likely to benefit and exclude those with little likelihood of benefit, and LIT during a pregnancy may significantly improve success rates. Keywords: Lymphocyte immunotherapy, Recurrent miscarriage, Gestation, Perinatal outcomes